2016
DOI: 10.1007/s10616-016-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

H3K9ac involved in the decondensation of spermatozoal nuclei during spermatogenesis in Chinese mitten crab Eriocheir sinensis

Abstract: As a well-known crustacean model species, the Chinese mitten crab Eriocheir sinensis presents spermatozoa with decondensed DNA. Our aim was to analyze structural distribution of the histone H3 and its acetylated lysine 9 (H3K9ac) during spermatogenesis for the mechanistic understanding of the nuclear decondensation of the spermatozoa in E. sinensis. Using specific antibodies, we followed the structural distribution and acetylated lysine 9 of the histone H3 during spermatogenesis, especially spermiogenesis, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…However, the mechanism of nuclear decondensation of latter yet needs to further study although some roles of many genes and (or) their encoding proteins involved in the spermatogenesis of E . sinensis had been reported [ 4 9 , 21 27 ]. The transcriptome traits of developing testes would give us a window to look at the tip of the iceberg of the relevant issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of nuclear decondensation of latter yet needs to further study although some roles of many genes and (or) their encoding proteins involved in the spermatogenesis of E . sinensis had been reported [ 4 9 , 21 27 ]. The transcriptome traits of developing testes would give us a window to look at the tip of the iceberg of the relevant issue.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors determine the compactness state of the chromatin, such as histones and histone binding proteins, modification of histones, DNA modification and DNA binding proteins. Recent research has found that the acetylation and the decrease of histones maybe contribute to the decondensation of chromatin [ 9 ]. Our results showed that 583 predicted genes might relate to the decondensation of chromatin in spermatozoal nucleus in E .…”
Section: Discussionmentioning
confidence: 99%
“…成过程中,只有少量的组蛋白 H2B 和 H3 残留在成熟的精子中 [32] ;同样在罗氏 沼虾(Macrobrachium rosenbergii)的成熟精子中发现,精子细胞核保有少量的 组蛋白 H3 和 H2B [33] [34] 。Niksirat 等人利用质谱技术在奥斯塔欧 洲螯虾 (Astacus astacus) 的精荚蛋白提取液中检测到组蛋白 H3 及 H4 的存在 [35] , 由于奥斯塔欧洲螯虾的精子被上皮细胞分泌的嗜碱性物质所形成的精荚包裹,因 此质谱结果鉴定的组蛋白 H3 及 H4 属于精子中的蛋白成分。 Wu 等人通过克隆中 华绒螯蟹(Eriocheir sinensis)组蛋白 H3 [36] 、H4 [37] 、H2B [38] 、H2A [39] 的基因序 列,发现中华绒螯蟹组蛋白 H3、H4 同人和小鼠相比,氨基酸序列相似性高达 99%,而组蛋白 H2B 和 H2A 的序列相似性仅在 80%左右,此外利用免疫荧光技 术发现组蛋白 H3、H4、H2B 和 H2A 定位于中华绒螯蟹成熟精子的细胞核中 [36,[38][39][40] [8,42] 。有研究表明,十足目动物黄道蟹和蜘蛛蟹成熟精子中的组蛋白 H4、 H3、H2B 均会发生乙酰化修饰,而且组蛋白 H4 的乙酰化修饰程度要高于组蛋白 H3 和 H2B 中的乙酰化修饰 [30,31] 。 之后在中国明对虾中同样发现精子的细胞核中 残留少量的乙酰化修饰组蛋白 H4 [34] 。以上的的研究结果虽然表明十足目甲壳动 物精子中存在乙酰化修饰的组蛋白, 但是乙酰化修饰的组蛋白对于非浓缩核形成 的功能还未可知。在 Wu 等人研究的基础上,Zhang 等人通过比较正常中华绒螯 蟹及性早熟中华绒螯蟹精子发生过程中组蛋白(H2A+H4) S1ph 的变化, 研究结果 表明中华绒螯蟹成熟精子组蛋白 H2A 和 H4 与精子非浓缩染色质结构密切相关 [40] 。此外,Zhang 等人还发现,虽然正常中华绒螯蟹以及性早熟中华绒螯蟹精子 发生过程中 H4S1ph 的含量无显著差异,但是性早熟中华绒螯蟹精子中 H4S1ph 的含量显著高于正常中华绒螯蟹精子,因此推测 H4S1ph 可以作为中华绒螯蟹精 子成熟度的一个标记物 [43] 。Li 等人通过对中华绒螯蟹精子发生过程组蛋白 H3K9ac 进行定位,研究发现组蛋白 H3K9ac 参与精子形成过程,而且 H3K9ac 定位于成熟精子的细胞核中,猜测 H3K9ac 参与精子形成过程中基因的调控以及 精子非浓缩核的包装 [44]…”
Section: A C C E P T E Dunclassified
“…It has been hypothesized that the hyperacetylation of histone H4 in spermatids can open the higher-order chromatin structure to facilitate the replacement of histones by transition nuclear proteins (TPs) or protamine during mouse and rainbow trout spermatogenesis (Christensen, Rattner, & Dixon, 1984;Hazzouri et al, 2000). Kurtz et al (2009) and Li et al (2017) found that histone H3 in the sperm nuclei of the brachyuran crab is acetylated. The noncondensed nucleus may be caused by remanent acetylated histone H4 accompanied by chromatin fibers in Fenneropenaeus chinensis (Ge et al, 2011).…”
Section: Histone Modifications Regulate Chromatin Statusmentioning
confidence: 99%
“…Earlier research indicated that the chromatin of crustacean sperm is not highly packaged due to a lack of basic proteins. However, several studies on Cancer pagurus (Kurtz, Martínez-Soler, Ausió, & Chiva, 2008), Cancer magister (Kurtz et al, 2008), Maja brachydactyla (Kurtz, Ausió, & Chiva, 2009), Portunus pelagicus (Stewart et al, 2010), Fenneropenaeus chinensis (Ge et al, 2011), Astacus (Niksirat, James, Andersson, Kouba, & Kozák, 2015), and Eriocheir sinensis (Li et al, 2017;Wu et al, 2016;Wu, Kang, Guo, Mu, & Zhang, 2015;Zhang et al, 2016) have indicated that these decapod spermatozoal nuclei have a common characteristic, namely, that they contain parts of histones and some histone modifications. Because of the diversity of crustacean species, an integrated understanding of the origin of this special decapod sperm nuclei has not been achieved.…”
mentioning
confidence: 99%